The critical natural capital of the Buffalo City Municipality, South Africa : harnessing local action for biodiversity conservation - Hagen, Brett (Rhodes University, Faculty of Science, Department of Environmental Science, 2011)
Globally, ecosystems provide services of almost twice the value of global gross national product (Costanza et al., 2006). The Buffalo City Municipality (BCM), South Africa contains biodiversity of national and international importance (Pierce, 2003; Pierce et al., 2005). Despite this, the municipality continues to experience loss of both urban and rural biodiversity (Buffalo City Municipality, 2006a). This study sought to determine the status of biodiversity, and the potential for ecosystem services to contribute to conservation, within the BCM. Biodiversity features, including ecosystem type, species of special concern and biodiversity processes, were identified and mapped using a GIS to produce a biodiversity priority index for the BCM. Current transformation status was then mapped to determine the level of ecosystem degradation within the BCM. Priority biodiversity areas as well as individual biodiversity features were spatially overlain against current transformation status and protected areas and analysed using a GIS to determine the level of degradation and protection of BCM biodiversity. In total 3.5 % of total BCM biodiversity was protected. Of the 24 ecosystem types, 11 (45%) had less than 1% under protection, while 16 (67%) had less than five percent protected. Not restorable areas, thus completely lost to biodiversity conservation, comprised just less than a quarter of the total BCM area while un-impacted areas comprised just 12.3%. Twenty five ecosystem services were identified as being provided by intact natural ecosystems within the BCM. The natural capital providing these services was identified and mapped to produce an ecosystem service index (ESI) using a GIS. This ecosystem service index and the biodiversity priority index were overlain to determine their level of correlation. Overall ESI correlation with priority biodiversity was weak although several individual ecosystem services, including carbon sequestration, showed correlation. Using the above data layers an implementation plan and conservation framework was proposed to assist the coordination of local conservation action within the BCM. It is concluded that ecosystem services are a potentially useful tool for conservationists at the local level seeking to ensure that biodiversity has relevance to and receives protection from broader society.
Keywords: Natural resources -- South Africa -- Buffalo City; Biodiversity conservation -- South Africa -- Buffalo City; Ecosystem services -- South Africa -- Buffalo City; Nature conservation -- South Africa -- Buffalo City; Environmental protection -- South Africa -- Buffalo City; Environmental degradation -- South Africa -- Buffalo City; Restoration ecology -- South Africa -- Buffalo City